2018
DOI: 10.1371/journal.pone.0191486
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of presepsin in adult patients with sepsis: Systematic review and meta-analysis

Abstract: ObjectivePresepsin is a novel biomarker to diagnose sepsis but its prognostic value has not been comprehensively reviewed. We conducted this meta-analysis to evaluate the mortality prediction value of presepsin in sepsis.MethodsWe searched comprehensive electronic databases from PubMed, EMBASE, and Cochrane Library through September 2017 using the key words of (‘presepsin’ or ‘sCD14-ST’ or ‘soluble CD14 subtype’) and (‘sepsis’ or ‘septic shock’) and (‘prognosis’ or ‘prognostic value’ or ‘prognostic biomarker’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 38 publications
(111 reference statements)
7
57
0
3
Order By: Relevance
“…Yang and co-authors performed systematic review and meta-analysis of prognostic value of presepsin in adult septic patients and concluded that 1 st day presepsin levels had prognostic value to predict mortality in adult patients with sepsis regardless of sepsis severity. However, they noted that further research is warranted for unified clinical information (15). In accordance with our results are findings from Behnes and co-authors, who assessed prognostic utility of presepsin in 116 critically ill septic patients (16).…”
supporting
confidence: 91%
“…Yang and co-authors performed systematic review and meta-analysis of prognostic value of presepsin in adult septic patients and concluded that 1 st day presepsin levels had prognostic value to predict mortality in adult patients with sepsis regardless of sepsis severity. However, they noted that further research is warranted for unified clinical information (15). In accordance with our results are findings from Behnes and co-authors, who assessed prognostic utility of presepsin in 116 critically ill septic patients (16).…”
supporting
confidence: 91%
“…Several biomarkers have been developed for the diagnosis of sepsis such as procalcitonin and C-reactive protein, but they have limitations in their use like sensitivity and specificity problems (2). Furthermore, sCD14-subtypes (presepsin) were discovered as a new biomarker for sepsis in 2004 and several studies have been conducted to delineate the importance of presepsin for early diagnosis and follow up of sepsis (13,33,34). It is well known that presepsin is produced in response to phagocytosis of bacteria in infections, however, it is not yet clear which humoral and cellular factors are responsible for the production of presepsin (13,35).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in subgroups, divided by the sepsis severity, pooled SMD for presepsin was significantly higher in non-survivors (P < 0.05). According to the authors' opinion, their results indicated some mortality prediction value of presepsin in patients with sepsis but defining the optimal cutoff point of presepsin requires further studies [38].…”
Section: Role Of Presepsin In Sepsismentioning
confidence: 96%
“…Yang et al [38] in adult septic patients assessed in a meta-analysis the prognostic value of presepsin. Ten studies and 1617 patients were included.…”
Section: Role Of Presepsin In Sepsismentioning
confidence: 99%